DEM analyses of shear band in granular materials. Issue 4 (15th June 2015) - Y.T. Feng, Professor Xikui Li, Professor Yuangqiang Tan; Professor Shunying Ji, Professor; Jiang, Mingjing; Zhang, Wangcheng
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Shear-induced strain localization in granular materials has been a hot topic under intensive research during the last four decades. However, the micromechanical process and mechanisms underlying the initiation and development of shear bands are still not fully understood. The purpose of this paper is to eliminate this deficiency. Design/methodology/approach – The paper carries out several two-dimensional distinct element method simulations to examine various global and local micromechanical quantities particular the energy dissipation and local stress and strain invariants with a special emphasis on the initiation and propagation of shear bands. Moreover, the effects of various influential variables including initial void ratio, confining stress, inter-particle friction coefficient, rolling resistance coefficient, specimen slenderness and strain rate on the pattern, scope and degree of shear bands are investigated. Findings – Novel findings of the relationship between sliding and rolling dissipation band and shear band are achieved, indicating a plastic dissipation nature for the shear band. The high inter-particle sliding or rolling resistance, relative small initial void ratio, relative low confining stress and high strain rate facilitate the formation of shear band. In addition, the specimen slenderness affects the pattern of shear band. Originality/value – In this paper, a comprehensive and deep investigation on shear band formation linked with localization of energy dissipation and strain invariants was presented. The new findings on particle scale during shear band formation helps to develop robust micromechanics-based constitutive models in the future.